Inoculação com azospirillum brasilense em milho na integração lavoura-pecuária e a relação com as doses de nitrogênio e umidade do solo e ph s em solução - Schaefer, Paulo Eugênio (2016)
Continuous use of fertilizer in high concentrations has been raising concerns on environmental pollution associated with the modernization and specialization of agricultural production and livestock systems. With this, consumers are understandably concerned and demand that production in agricultural systems be combined with sustainability and production efficiency. The purpose of this study was to evaluate the agronomic performance of maize inoculated with Azospirillum brasilense and different doses of nitrogen in crop-livestock integration system managed with different post-grazing forage masses and interference of abiotic factors on the vegetative development of the crop. Three studies were conducted, one in the field and two in a protected environment. The field study was conducted in the municipality of Mata, in a Rhodic Paleudalf, in the experimental design of randomized blocks with sub-divided plots, three repetitions, in factorial scheme of 5x2x5 (post-grazing forage mass, Azospirillum brasilense and doses of nitrogen). The heights of the post-grazing forage mass were 0.10m, 0.20m, 0.30m, conventional grazing and without grazing, with doses of nitrogen that varied between 0.75, 150, 225 and 300 kg ha-1, with and without inoculation. Studies began in the year 2014, with the management of the forage in two winters and two years of assessing the crops at field level in the agricultural years of 2014/2015 and 2015/2016. The other two studies in protected environment were conducted at the Federal University of Santa Maria, from November 2015 to April 2016. The treatments in the first study were maize inoculated or not, in nutrient solution with five variations of pH (4.5; 5.0; 5.5; 6.0 and 6.5), in bifatorial arrangement with three repetitions. In the second experiment, different levels of soil humidity with and without inoculation were evaluated, with four repetitions in soil moisture field capacity of 25%, 50%, 75% and 100%. Both studies used the hybrid DEKALP 240 and inoculant "AzoTotal" (liquid). The field study was evaluated the agronomic traits and yield components of maize, from the beginning to the end of the crop cycle. In the studies conducted in a protected environment, evaluations of the shoot and root system occurred until the phenological stage V4. In the field study, the analysis of inoculation observed an increase of 13% for use of Azospirillum brasilense in the treatment of maize seed for the 2014/2015 harvest. Azospirillum brasilense provided an increase in productive gain of 4.5% in regards to its absence. It was possible to observe, therefore, that plants with the presence of the bacteria improve their root system in soil with hydric stress. When the root volume increased, part of the shoot of the crop decreased. The use of diazotrophic bacteria contributed to the increment of the photosynthetic pigments in the maize leaves when in water deficit. Root and shoot development of maize were affected by the variation of pH of solution. Given these results, the presence of Azospirillum brasilense favors plant growth, increases root volume and improves grain productivity, especially in years of cultivation with less precipitation during the stage of plant growth. The presence of Azospirillum brasilense extends the magnitude of pH with possibility of cultivation for maize.